2010
DOI: 10.1128/mcb.00322-09
|View full text |Cite
|
Sign up to set email alerts
|

Mitotic Raptor Promotes mTORC1 Activity, G2/M Cell Cycle Progression, and Internal Ribosome Entry Site-Mediated mRNA Translation

Abstract: The mTOR signaling complex integrates signals from growth factors and nutrient availability to control cell growth and proliferation, in part through effects on the protein-synthetic machinery. Protein synthesis rates fluctuate throughout the cell cycle but diminish significantly during the G 2 /M transition. The fate of the mTOR complex and its role in coordinating cell growth and proliferation signals with protein synthesis during mitosis remain unknown. Here we demonstrate that the mTOR complex 1 (mTORC1) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
112
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 74 publications
7
112
5
Order By: Relevance
“…In prophase, the RNA . 7 As mentioned above, AMPK has been shown to directly phosphorylate Raptor at Ser 722 . 13 In this regard, we have previously reported that the active form of AMPK directly binds the mitotic apparatus and travels from centrosomes to the spindle midzone during mitosis.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…In prophase, the RNA . 7 As mentioned above, AMPK has been shown to directly phosphorylate Raptor at Ser 722 . 13 In this regard, we have previously reported that the active form of AMPK directly binds the mitotic apparatus and travels from centrosomes to the spindle midzone during mitosis.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Given this complexity, ULK1-mediated Raptor phosphorylation may be an epiphenomenon. As Raptor is phosphorylated by many positive and negative signaling inputs, [20][21][22][23][24][25][26] it is likely that the Raptor phosphorylation events observed by either overexpression or knockdown of ULK1 contribute to the regulation of mTORC1. It is highly probable that other factors will contribute to this negative feedback mechanism, which could include phosphorylation as playing an important role in autophagy induction.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…It is known that phosphorylation of Raptor by RSK, 21 ERK1/2, 26 AMPK 20 or during mitosis 23 can modulate the activity of mTORC1. Therefore, to determine whether ULK1-mediated phosphorylation of Raptor could modulate mTORC1 signaling, we analyzed the activity of the downstream substrate S6K1 and the phosphorylation of 4E-BP1 in the presence or absence of ULK1 overexpression.…”
Section: Ulk1 Induces Phosphorylation Of Raptormentioning
confidence: 99%
See 2 more Smart Citations